2019
DOI: 10.2147/copd.s207400
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of vitamin D on spirometry findings and quality of life in patients with chronic obstructive pulmonary disease: a randomized, double-blinded, placebo-controlled clinical trial</p>

Abstract: COPD is an irreversible chronic illness with airflow limitation. The aim of the current study was to assess the role of vitamin D 3 on quality of life and pulmonary function in patients with COPD. A randomized, double-blinded clinical trial was conducted in 63 patients with COPD. Patients were placed into intervention and placebo groups. Each individual in the intervention group took 50,000 IU vitamin D 3 once a week for 8 weeks and then once a month for 4 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…For example, Bai and Dai ( 39 ) proposed that increased serum vitamin A and 25-hydroxyvitamin D3 (25OHD 3 ) levels can reflect the lung function and quality of life of asthmatic children. Vitamin D supplementation can improve the quality of life of patients with chronic pulmonary obstruction ( 40 ). In this study, quality of life scores were observed and counted in the RG and CG.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bai and Dai ( 39 ) proposed that increased serum vitamin A and 25-hydroxyvitamin D3 (25OHD 3 ) levels can reflect the lung function and quality of life of asthmatic children. Vitamin D supplementation can improve the quality of life of patients with chronic pulmonary obstruction ( 40 ). In this study, quality of life scores were observed and counted in the RG and CG.…”
Section: Discussionmentioning
confidence: 99%
“…Both single high dose intramuscular and oral supplemental vitamin D seems to have beneficial effects on health-related quality of life [ 42 , 38 ]. We could not find many trials on mortality or disease prognosis as a primary outcome.…”
Section: Reviewmentioning
confidence: 99%
“…But later on, many studies showed similar results as Lehouck et al and added to the hypothesis that people with low serum 25(OH)D levels benefit more from supplemental vitamin D [ 31 , 42 , 43 ]. Many authors attributed their failure to obtain the desired outcome to either inclusion of vitamin D sufficient samples or the exclusion of vitamin D deficient COPD patients [ 37 , 38 , 41 ]. Other than vitamin D deficient or insufficient population, ever smokers with hypovitaminosis D or asthma/COPD are the groups who can get more benefits from the use of vitamin D as a therapeutic agent [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Though limited by their small sample size, some randomized controlled trials have reported improvements in exacerbations, 6-minute walk distance, or symptoms as measured by the COPD Assessment Test. [41,42] Longitudinal cohorts of COPD populations similarly demonstrate increased exacerbations, accelerated FEV1 decline, and higher symptom burden in association with lower vitamin D levels. [43] Our study had several other important limitations.…”
Section: Association Between Obstructive Lung Disease and Serum 25(oh)dmentioning
confidence: 99%